Digital Transformation in Pesantren Education to Enhance Work Readiness Among Students: A Comparative Case Study - Dimyathi, Mohammad Syairozi; Muchammad, Putra Bagus; Thabrani, Hannanah Mukhtar; Syairozi, Nurhan M. (GoAcademica Research & Publishing, 2025)
Digital transformation in Islamic boarding school education (pesantren) has become a strategic necessity in the era of the Industrial Revolution 4.0 and Society 5.0. This study aims to analyze the forms, strategies, and effectiveness of digital transformation in three modern Vocational High School Boarding School (VHS BS): ABC VHS BS (Bogor Regency), PQR VHS BS (West Bandung Regency), and XYZ VHS BS (Bandung Regency) as well as its impact on enhancing students’ employability skills. The research employs a qualitative approach with a multi-case study design. Data were collected through semi-structured interviews, observations, and document analysis, including digital policy documents, e-learning modules, and alumni employment data from 2022-2025. Thematic analysis was conducted based on Change Management, TPACK, and Dynamic Capabilities theories. The findings reveal that digital transformation in VHS BS encompasses four main dimensions: (1) digital policy and infrastructure, (2) capacity building for teachers and students, (3) technology integration in vocational and Islamic curricula, and (4) strengthening students’ digital employability skills. The implementation of digitalization has proven to enhance digital literacy, professional communication, collaboration, and Islamic work ethics. The success of digital transformation is determined by visionary leadership, human resource readiness, industry partnerships, and the internalization of spiritual values within the organizational culture of the pesantren. Theoretically, this study introduces a new concept of Digital Employability Skills Santri, which integrates technological competence, Islamic character, and industry relevance as the foundation for work readiness in the digital era. The findings contribute to the development of a conceptual model for digital transformation in Islamic education and provide strategic recommendations for implementing Indonesia’s Digital Education Roadmap 2030.